Preparation and evaluation of fermented Ayurvedic formulation: Arjunarishta - S. F. Sayyad, D. S. Randive, S. M. Jagtap, S. R. Chaudhari, B. P. Panda (Journal of Applied Pharmaceutical Science)
Growing awareness about harmful side effects of modern medicine has led to interest in Ayurveda at the international level as well as within India. Ayurveda comprises of various types of formulations including fermented forms, namely, arishtas and asavas. Arishtas are regarded as unique and valuable therapeutics due to their efficacy, stability and desirable features. It prepared using decoction of herbal drug and contains self generated alcohol. Although these formulations are mentioned in traditional literature and used regularly their scientific investigation and reporting is essential to strengthen Ayurveda in global market. In present study attempt has been made for preparation and evaluation of arjunarishta. Terminalia arjuna is a active constituent of arjunarishta and prescribed in cases of cardiovascular diseases as a cardiotonic. 6.42% w/w alcohol was generated after fermentation of traditionally prepared arjunarishta formulation. It is palatable to use due to sweet taste combined with fine aroma which masks unpleasant taste and odour of added herbal ingredients.
Keywords: Ayurveda, fermented formulation, arishta.